An Analysis of Figurative Language in Adele’s Songs Easy on Me and When We Were Young - Salam, Trisnayanti; Kumayas, Tirza A.; Sabudu, Delli (Program Studi Pendidikan Bahasa Inggris, 2024)
The title of this research is